Removal Characteristics of Organic Pollutants from Eutrophic Raw Water by Biological Pretreatment Reactors - Guangcan Zhu; Zhonglian Yang; Xiwu Lu (Journal of Chemistry)
Two biological contact oxidation reactors, cascade biofilm reactor (CSBR) and one-step biofilm reactor (OSBR), were used in this paper for pretreatment of eutrophic water from Lake Taihu in China. The CSBR was more effective and stable for eutrophic water treatment than OSBR, in terms of extracellular microcystin-LR, chlorophyll-a, DOC, and biodegradable dissolved organic carbon (BDOC) removal. Removal efficiencies of extracellular microcystin-LR and chlorophyll-a were 75.8% and 59.7% in CSBR and 60.5% and 53.0% after 2 h in OSBR. CSBR had much higher removal efficiency (34.3%) than OSBR (22.7%) for DOC, and CSBR could remove 67% BDOC, accounting for 34% of total DOC in source water. 11.5% of DOC was removed through means other than biological degradation, such as biofilm adsorption and bioflocculation. In CSBR at 5.5~13°C, 57.5% of atrazine was removed at 2 h hydraulic retention time, with background concentration of 136.5 ng/L. Meanwhile, removal efficiencies of three phthalic acid esters (PAEs) (dimethyl phthalate, di-(2-ethylhexyl) phthalate, and di-n-butyl phthalate) were 78.7%, 52.4%, and 85.3%, respectively. Only 35.2% of polycyclic aromatic hydrocarbons (PAHs) could be removed by CSBR with initial concentration of 21.5 μg/L. The results indicated that CSBR is effective in low-molecular-weight organic pollution pretreatment and provides benefits in terms of effluent quality.